Solar engineering of thermal processes - Duffie, John A.; Beckman, William A. (New York : John Wiley and Sons, 1991)
This book is divided into three parts: Fundamentals of Solar Engineering; Applications of Solar Engineering; and Thermal Design Methods.
Keywords: Heat; Solar energy; Transmission; Solar energy; Heat -- Transmission